Pengaruh Variasi Arah Aliran Udara pada Stove terhadap Karak-teristik Pembakaran Wood Pellet - Yuliati, Lilis; Simanungkalit, David (Jurnal Rekayasa Mesin, 2020)
This research was conducted to investigate the effect of inlet airflow direction on the combustion characteristics of a wood pellet stove. The direction of the airflow into the wood pellet stove is varied for four methods, namely inlet I, inlet II, inlet III, and inlet IV. At inlets, I, II, and III air is injected into the plenum in the radial direction with the injection points at r = -8, 0, and 8 cm respectively, whereas at inlet IV the direction of airflow into the plenum is in the axial direction with the injection point at r = 0. The combustion characteristics were observed in the wood pellet stove with a continuous fuel feeding system. The combustion characteristics investigated in this research consist of flame visualization, flame temperature, combustion rate, and the efficiency of the wood pellet stove. The results showed that wood pellet stoves with inlet IV had a lower combustion rate and flame height, however, this stove indicates a higher flame temperature and stove efficiency. Air entrance through the inlet IV induces most of the airflow to enter the combustion chamber through the primary channel, compared to that through the secondary and tertiary channels. The primary airflow through the wood pellet encourages a better devolatilization and combustion process. These conditions conduce the flame dimension which is a zone where the combustion reaction occurs is smaller with a higher flame temperature, due to higher volumetric heat release rate. This matter results in better heat transfer from the flame to the test fluid and higher stove efficiency.